Titanium oxide cluster cavity confinement monatomic copper catalyst as well as preparation method and application thereof

By anchoring copper atoms within the cavities of titanium-oxygen clusters to form confined single-atom copper catalysts, the problems of uneven metal site distribution and agglomeration in traditional catalysts are solved, achieving efficient and stable photoelectrocatalytic urea synthesis, reducing energy consumption and improving CN coupling selectivity.

CN120945422APending Publication Date: 2025-11-14SHANDONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511111203.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing photoelectrocatalysis technologies in urea synthesis suffer from high reaction overpotentials, low CN coupling selectivity, and unclear mechanisms. Traditional catalysts also exhibit uneven metal site distribution and are prone to migration and aggregation, leading to unstable catalytic performance.

Method used

Titanium oxide clusters with large cavities were synthesized by a solvothermal method. Copper atoms were anchored in the cavities using NaBH4 as an auxiliary reducing agent to form a single-atom copper catalyst confined within the titanium oxide cluster cavity. This achieved precise doping and dispersion of copper atoms. Combined with Cu-3d/Ti-3d orbital hybridization, the synergistic effect of active sites was optimized.

Benefits of technology

It significantly improves the selectivity and stability of urea synthesis, reduces energy consumption, achieves efficient co-reduction of CO2 and NO3-, increases urea yield by more than 3 times under ultraviolet light, suppresses hydrogen evolution side reaction, and the copper sites maintain 80% activity in continuous reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120945422A_ABST
    Figure CN120945422A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-oxygen cluster cavity confinement monatomic copper catalyst as well as a preparation method and application thereof, and relates to the field of material science and photoelectrocatalysis. The method for preparing the titanium oxide cluster cavity confinement monatomic copper catalyst comprises the following steps: firstly preparing a titanium oxide cluster with a large cavity structure, and then coordinating and anchoring copper ions and water molecules in a cavity by using the assistance of NaBH4 to obtain the titanium oxide cluster cavity confinement monatomic copper catalyst. According to the method, the Ti16 precursor is firstly synthesized, and then Cu is directionally anchored in the cavity through NaBH4-assisted reduction, so that the defect of non-uniform metal distribution caused by a traditional one-pot method is overcome, high yield and good reproducibility of the catalyst are realized, and industrial requirements are met. According to the titanium oxide cluster cavity confinement monatomic copper catalyst Ti16 cluster prepared by the method disclosed by the invention, a rigid cavity formed by an octagonal prism framework can efficiently anchor copper atoms, so that the problem of migration and agglomeration of metal sites in a traditional catalyst is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of materials science and photoelectrocatalysis, specifically to a titanium-oxygen cluster cavity-confined single-atom copper catalyst, its preparation method, and its application. Background Technology

[0002] Urea, an important nitrogen fertilizer and chemical raw material, is traditionally synthesized using the Haber-Bosch process, which requires high temperature and pressure (150-200 atm, 400-500℃), resulting in high energy consumption and carbon emissions. In contrast, photoelectrocatalysis (PEC) technology utilizes solar energy to produce CO2 and NO3. - Using photocatalysis (PEC) as a raw material to synthesize urea at room temperature and pressure, it combines the advantages of photocatalysis (highly efficient light absorption) and electrocatalysis (precise potential control). However, PEC technology still faces challenges such as high reaction overpotential, low CN coupling selectivity, and unclear mechanism, which restrict its practical application. Developing efficient and stable catalyst systems has become a current research focus.

[0003] Titanium-based materials have shown promising potential in urea synthesis due to their strong adsorption capacity for nitrogen-containing molecules. Among them, titanium oxide clusters (TOCs), as molecular-level models, have advantages such as well-defined structures and tunable coordination environments: (1) efficient charge separation enhances light energy utilization; (2) active sites can be optimized through ligand modification or metal doping; (3) strong N adsorption can suppress hydrogen evolution side reactions. However, TOCs still have limitations such as a narrow light absorption range (mainly limited to the ultraviolet region) and the difficulty of synergistic activation of CO2 / NO3 by a single Ti site. - Problems such as poor stability of cluster structures necessitate material modification to improve performance.

[0004] Heterometallic doping is an effective strategy for improving the performance of total organic carbon (TOCs). Copper-doped titanium-oxygen clusters can lower the CN coupling barrier through Cu-3d / Ti-3d orbital hybridization, while the cavity energy of the titanium-oxygen clusters confines copper atoms, preventing their aggregation. This dual-site (Cu-Ti) synergistic effect can match CO2 / NO3. - The kinetic differences in reduction significantly improve reaction performance. However, traditional synthesis methods struggle to precisely control heterometallic doping, leading to uneven distribution of active sites; and existing catalysts still face challenges such as low charge separation efficiency and unclear intermediate adsorption-activation mechanisms.

[0005] Therefore, developing a dual-active-site synthesis method that can synergistically catalyze the reduction of carbon dioxide and nitrate (especially by using the strategy of confining copper atoms in titanium-oxygen clusters) provides a new approach for achieving green and low-energy urea synthesis. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a titanium-oxygen cluster cavity-confined single-atom copper catalyst, its preparation method and application. By anchoring copper atoms through the cluster cavity confinement effect, the invention solves the problems of uneven metal site distribution and easy migration and aggregation of traditional catalysts. By introducing copper ions, the selectivity of urea synthesis is improved, the adsorption activation mechanism is elucidated, a simple synthesis method is developed, and gram-scale preparation and recycling of the catalyst are realized, effectively overcoming the technical barriers existing in the prior art.

[0007] To achieve the above or other objectives, the present invention is implemented through the following technical solutions.

[0008] A method for preparing a titanium-oxygen cluster cavity-confined single-atom copper catalyst includes the following steps:

[0009] 1) Synthesis of titanium dioxide clusters (Ti 16 Benzoic acid and hexamethylenetetramine were added to a solvent, followed by formic acid. The mixture was stirred, and isopropyl titanate was added to initiate a solvothermal reaction. After the reaction was complete, post-treatment yielded titanium dioxide clusters (Ti). 16 ;

[0010] 2) Anchoring copper atoms inside the cavity: Under the protection of an inert gas, the titanium oxide clusters Ti obtained in step 1) are anchored... 16 Dispersed in tetrahydrofuran and stirred until dissolved, a reducing agent NaBH4 was added, followed by a degassed copper ion solution. Stirring continued, and after post-treatment, a titanium-oxygen cluster cavity-confined single-atom copper catalyst, i.e., Cu, was obtained. x @Ti 16 catalyst.

[0011] In this invention, the interaction between copper and Ti can be controlled. 16 The molar ratio is used to adjust the amount of copper doping. Preferably, x can be 0.25, 0.5, 1, 2, 4, or 8.

[0012] In one example of the present invention, in step 1), the molar ratio of benzoic acid, hexamethylenetetramine, formic acid, and isopropyl titanate is 12:(0.3-0.5):(1-3):(1.5-3). To ensure a complete reaction, formic acid is added dropwise.

[0013] In one example of the present invention, in step 1), the molar ratio of solvent to isopropyl titanate is (57-115):(1-3). Preferably, the solvent is selected from acetonitrile.

[0014] In one example of the present invention, in step 1), the solvothermal reaction temperature is 65℃~85℃ and the reaction time is 1d~5d.

[0015] In one example of the present invention, in step 1), the post-processing includes, but is not limited to, filtration and washing.

[0016] In one example of the present invention, the titanium oxide clusters Ti obtained in step 1) 16 The core size is 6nm to 12nm.

[0017] In one example of the present invention, in step 2), the titanium oxide clusters Ti 16 The mass ratio of the substance to tetrahydrofuran is 1:(27-67).

[0018] In one example of the present invention, in step 2), the titanium oxide clusters Ti 16 The mass ratio of NaBH4 to NaBH4 is (4-20):1.

[0019] In one example of the present invention, the copper ion solution in step 2) is obtained by the following treatment: anhydrous copper chloride is vacuum dried and then dissolved in a dehydrated organic solvent. Preferably, the dehydrated organic solvent can be selected from tetrahydrofuran, toluene, isopropanol, and acetonitrile. Preferably, the concentration of the copper ion solution is 0.08–3 mg / mL. Preferably, the vacuum drying temperature is 70°C–100°C. In the present invention, by adding the copper ion solution treated as described above, the purity of the product can be effectively improved, and the reduction of NaBH4 activity can be avoided.

[0020] In one example of the present invention, in step 2), the copper ion solution is added at a rate of 0.2 to 3 mL / min.

[0021] In one example of the present invention, in step 2), after the copper ion solution is added dropwise, stirring continues for 6h to 24h.

[0022] In one example of the present invention, the post-processing in step 2) includes centrifugation, filtration, and vacuum drying. Preferably, the centrifugation speed is 8000 rpm to 12000 rpm, and the centrifugation time is 5 min to 15 min. The vacuum drying temperature is 50℃ to 150℃, and the vacuum drying time is 1 h to 12 h.

[0023] This invention also provides a titanium-oxygen cluster cavity-confined single-atom copper catalyst prepared using the above-described preparation method. The titanium-oxygen cluster cavity-confined single-atom copper catalyst prepared by this invention has a cavity confinement... The dispersion of single-atom Cu is ensured, limiting the migration of Cu atoms. At the same time, hydrophobic ligands and a rigid Ti-O-Ti framework ensure its structural stability.

[0024] The third aspect of this invention also provides the application of the above-mentioned titanium-oxygen cluster cavity-confined single-atom copper catalyst in the photoelectrocatalytic reduction reaction to prepare urea.

[0025] A method for preparing urea using a photoelectrocatalytic reduction reaction employs the aforementioned titanium-oxygen cluster cavity-confined single-atom copper catalyst as the catalyst. The carbon source is selected from carbon dioxide, and the nitrogen source is selected from potassium nitrate.

[0026] Further, the method includes the following steps: a. Dispersing the catalyst in a mixed solution of Nafion and anhydrous ethanol to prepare a catalyst ink, uniformly coating the catalyst ink onto carbon paper, drying it, and using it as the working electrode, with Ag / AgCl as the reference electrode and Pt as the counter electrode to form a three-electrode system; b. In an H-type electrolytic cell, adding electrolyte, and under a high-purity CO2 atmosphere, treating it with light and periodic pulse voltage to achieve the co-reduction coupling of carbon dioxide and nitrate to synthesize urea.

[0027] In one example of the present invention, the mass ratio of catalyst to Nafion is (1-20):(27.5-110).

[0028] In one example of the present invention, the volume ratio of Nafion to anhydrous ethanol is 1:4.

[0029] In one example of the present invention, the electrolyte is a mixed solution of 0.01-0.2 mol / L KNO3 and 0.01-0.2 mol / L KHCO3.

[0030] In one example of this invention, the illumination conditions are: λ≤400nm, light intensity 142mW / cm². 2 Irradiation under ultraviolet light, with a photoreaction time of 2-20 hours and a phototemperature of 25±2℃.

[0031] In one example of the present invention, the periodic pulse voltage is -0.7V to -0.3V vs. RHE.

[0032] This invention provides a titanium oxide cluster cavity-confined single-atom copper catalyst and its preparation method. The method first prepares titanium oxide clusters with large cavity structures, which can be uniformly dispersed in tetrahydrofuran solution. Then, using NaBH4 as an aid, copper ions are coordinated and anchored with bridging oxygen within the cavity, maintaining stability within the structure and preventing copper atom aggregation. This invention can precisely control the introduction of copper atoms to regulate active sites and promote efficient CN-directed coupling. The final product has copper atoms anchored within the cavity of the titanium oxide cluster through bridging oxygen coordination, with each Cu atom coordinated to four μ2-O atoms. The Cu atoms confined within the titanium oxide cluster exist in a single-atom state. This single-atom dispersed Cu site may have a unique influence on the electron transfer process of CO2 / NO3- reduction (enhancing the activation ability of reaction intermediates). The titanium oxide cluster cavity-confined single-atom copper catalyst prepared by this invention exhibits faster photoelectrochemical catalytic activity for urea synthesis than titanium oxide clusters without copper introduction.

[0033] This invention has the following significant technical features and innovative advantages: (1) A confined catalytic system with precise and controllable structure: cavity confinement effect: Ti with a large cavity structure is synthesized by solvothermal method. 16 The clusters, with their rigid cavities formed by an octagonal prism framework, can efficiently anchor copper atoms (Cu-O coordination), avoiding the problem of metal site migration and aggregation in traditional catalysts. Single-atom copper active centers: EXAFS analysis shows that confinement within Ti... 16 The Cu in the sample exhibits a monoatomic dispersion. This monodisperse Cu sites improve atomic utilization and significantly enhance the performance against *CO. x and *NO x Efficiency of CN coupling in intermediates. Two-site cooperative mechanism: CN coupling energy barrier is lowered through Cu-3d / Ti-3d orbital hybridization, enabling CO2 and NO3 coupling. - (2) Efficient and scalable synthesis method: two-step precise doping: first synthesize Ti 16 The precursor is then reduced with NaBH4 to directionally anchor Cu within the cavity, overcoming the defects of uneven metal distribution in traditional one-pot methods (such as insufficient ligand coverage and uncontrollable thermodynamics). Gram-scale preparation process: Optimized reaction conditions (such as solvothermal reaction at 65-85℃, Cu / Ti...) 16 (Molar ratio regulation) to achieve high yield and good reproducibility of the catalyst, meeting industrial needs. (3) Excellent photoelectrocatalytic performance: Highly selective urea synthesis: Under ultraviolet light (λ≤400nm) and low bias voltage, Cu x @Ti 16 Urea yield was higher than that of undoped Ti 16 It improves efficiency by more than 3 times and suppresses hydrogen evolution side reactions (HER selectivity <10%). It also exhibits outstanding stability: Ti 16 The confinement effect of the framework allows Cu sites to retain 80% activity after 10 hours of continuous reaction, which is superior to traditional copper-based catalysts (such as Cu / TiO2 nanoparticles). (4) Broad application prospects: Green synthesis route: Urea is synthesized at room temperature and pressure using CO2 and nitrate as raw materials, which reduces energy consumption compared to the Haber-Bosch process. (5) Mechanism research platform: Ti 16 The well-defined molecular structure provides an atomic-level model for revealing the CN coupling mechanism, thus promoting rational catalyst design.

[0034] The titanium-oxygen cluster cavity-confined single-atom copper catalyst prepared by the method of this invention is used in the photoelectrocatalytic reduction reaction to produce urea. Utilizing the synergistic effect of light and electrical energy, it improves the separation efficiency of photogenerated electron-hole pairs and reduces the external bias voltage requirement, achieving efficient and low-energy-consumption urea synthesis at room temperature and pressure. Furthermore, this invention combines the synergistic effect of copper (Cu) active sites and titanium-oxygen clusters, optimizing the reaction of CO2 and NO3. - Co-activation lowers the reaction energy barrier and improves catalytic efficiency.

[0035] In summary, this invention solves the problems of low activity and poor stability of traditional catalysts through the synergistic design of structural confinement and high-valence copper sites, providing a new material system that is efficient and scalable for green urea synthesis. Attached Figure Description

[0036] Figure 1 Ti prepared in Example 1 16 Crystal structure of a single crystal (hydrogen is ignored for clarity).

[0037] Figure 2 The catalyst (Cu2@Ti) for confined single-atom copper within a titanium-oxygen cluster cavity prepared in Example 1 16 Scanning electron microscopy energy dispersive spectroscopy (SEM-EDS) of ).

[0038] Figure 3a The titanium oxide cluster cavity-confined single-atom copper catalysts (Cu) with different copper contents prepared in Examples 1-6 x @Ti 16 (Powder photo)

[0039] Figure 3b The titanium oxide cluster cavity-confined single-atom copper catalysts (Cu) with different copper contents prepared in Examples 1-6 x @Ti 16 The ratio of copper to titanium in ( ).

[0040] Figure 4a Example 1 shows the prepared titanium-oxygen cluster cavity-confined single-atom copper catalyst (Cu2@Ti). 16 ) and Ti 16 The infrared spectrum.

[0041] Figure 4b The titanium-oxygen cluster cavity-confined single-atom copper catalyst (Cu2@Ti) prepared in Example 1 16 ) and Ti 16 Raman spectra.

[0042] Figure 5 The titanium-oxygen cluster cavity-confined single-atom copper catalyst (Cu2@Ti) prepared in Example 1 16 Extended X-ray absorption fine structure spectra (EXAFS) of CuO, Cu2O, and Cu foil.

[0043] Figure 6a For example Cu2@Ti in Application Examples 1, 7 to 10 16 Urea yield under different bias voltages in the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to synthesize urea.

[0044] Figure 6bFor example Cu2@Ti in Application Examples 1, 7 to 10 16 The Faraday efficiency (FE) of the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to urea under different bias voltages.

[0045] Figure 6c For example Cu2@Ti in application example 1 16 As a catalyst, the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to synthesize urea was performed. After electrolysis for two hours at a bias voltage of -0.6V vs. RHE, the UV-Vis absorption spectrum of urea was determined by the diacetyl monooxime method.

[0046] Figure 6d For example Cu2@Ti in application example 1 16 As a catalyst, the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to urea was performed. After two hours of electrolysis at -0.6V vs. RHE bias, NO2 was determined using the Griess reagent method. - Ultraviolet-visible absorption spectrum.

[0047] Figure 6e For example Cu2@Ti in application example 1 16 As a catalyst, the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to synthesize urea was performed. After electrolysis for two hours at a bias voltage of -0.6V vs. RHE, the UV-Vis absorption spectrum of NH3 was determined by the salicylic acid method.

[0048] Figure 6f For example Cu2@Ti in application example 1 16 The gas chromatogram of the gaseous products after two hours of electrolysis at a bias voltage of -0.6V vs. RHE for the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to synthesize urea.

[0049] Figure 7a For example Cu2@Ti in application example 1 16 Its long-term stability is demonstrated when used as a catalyst in the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to synthesize urea.

[0050] Figure 7b For example Cu2@Ti in application example 1 16 The yield and FE at different reaction times were measured when the photoelectrocatalytic reaction of CO2 and potassium nitrate to synthesize urea was performed.

[0051] Figure 8a The urea yield is measured in Application Examples 1 to 6, Comparative Examples 1 and 2 during the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to urea, under a bias voltage of -0.6V vs. RHE for two hours.

[0052] Figure 8bThe Faraday efficiency (FE) of Application Examples 1 to 6, Comparative Examples 1 and 2 in the photoelectrocatalytic reduction reaction of CO2 and potassium nitrate to urea was measured for two hours under a bias voltage of -0.6V vs. RHE. Detailed Implementation

[0053] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. It should also be understood that the terminology used in the embodiments of the present invention is for describing specific implementation schemes and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or according to the conditions recommended by the respective manufacturers.

[0054] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" used in this specification are only for clarity of description and are not intended to limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered as part of the scope of the invention.

[0055] The technical solution of the present invention will be described in detail below through several specific embodiments and comparative examples. Unless otherwise stated, the raw materials and reagents used in the following embodiments are commercially available products, or can be prepared by conventional methods in the art. Unless otherwise specified, the detection methods used in the embodiments of the present invention are conventional detection methods in the industry. Unless otherwise specified, all raw materials used in the present invention are commercially available.

[0056] Example 1

[0057] Copper-anchored high-nucleus titanium oxide clusters (Cu2@Ti) 16 The preparation method of ) is as follows:

[0058] (1) In a 20 mL vial, benzoic acid (1.46 g, 12.00 mmol) and hexamethylenetetramine (0.06 g, 0.43 mmol) were dispersed in 4 mL of acetonitrile. After stirring, formic acid (15 drops, 0.30 mL) was added dropwise, followed by isopropyl titanate (0.92 mL, 3.00 mmol). The mixture was stirred thoroughly to obtain a clear solution. The vial was then sealed and heated in an 80 °C oven for 3 days. During the heating process, colorless blocky crystals were formed, which were titanium dioxide clusters (Ti). 16 (The yield based on Ti was 30.7%).

[0059] (2) In a 100mL round-bottom flask, add Ti 16 Disperse 0.10 g of the catalyst into 10 mL of tetrahydrofuran and stir thoroughly until dissolved. After purging with nitrogen for 20 min, add 10.00 mg of reducing agent NaBH4 and stir thoroughly for 2 h. Then add anhydrous copper chloride solution (6.6 mg dispersed in 1 mL of tetrahydrofuran and pre-degassed) at a drop rate of 0.5 mL / min and stir overnight. Centrifuge (12000 rpm for 5 min), filter, and dry the resulting solution by rotary evaporation (100 °C for 5 h) to obtain the catalyst Cu2@Ti. 16 .

[0060] Example 2

[0061] Titanium oxide clusters Ti were prepared using the same method as in Example 1. 16 In a 100mL eggplant-shaped flask, add Ti 16 Disperse (0.10 g) in 10 mL of tetrahydrofuran, stir thoroughly until dissolved, purge with nitrogen for 20 min, add reducing agent NaBH4 (10.00 mg), stir thoroughly for 2 h, then add anhydrous copper chloride solution (0.825 mg dispersed in 1 mL of tetrahydrofuran, pre-degassed), stir overnight, centrifuge, filter, and rotary evaporate and dry to obtain catalyst Cu. 0.25 @Ti 16 .

[0062] Example 3

[0063] The preparation method of copper-anchored high-nucleus titanium oxide cluster material described in Example 2 differs in that:

[0064] Anhydrous copper chloride solution (1.65 mg dispersed in 1 mL tetrahydrofuran) was added to finally obtain the catalyst Cu. 0.5 @Ti 16 .

[0065] Example 4

[0066] The preparation method of copper-anchored high-nucleus titanium oxide cluster material described in Example 2 differs in that:

[0067] Anhydrous copper chloride solution (3.3 mg dispersed in 1 mL tetrahydrofuran) was added to finally obtain the catalyst Cu1@Ti. 16 .

[0068] Example 5

[0069] The preparation method of copper-anchored high-nucleus titanium oxide cluster material described in Example 2 differs in that:

[0070] Anhydrous copper chloride solution (13.2 mg dispersed in 1 mL tetrahydrofuran) was added to finally obtain the catalyst Cu4@Ti. 16 .

[0071] Example 6

[0072] The preparation method of copper-anchored high-nucleus titanium oxide cluster material described in Example 2 differs in that:

[0073] Anhydrous copper chloride solution (26.4 mg dispersed in 1 mL tetrahydrofuran) was added to finally obtain the catalyst Cu8@Ti. 16 .

[0074] Example 7

[0075] The difference between this embodiment and Example 1 is as follows: In this embodiment, the solvothermal reaction temperature is 65℃, the reaction time is 5 days; the copper ion solution is added at a rate of 3 mL / min; the centrifugation speed in step 2 is 10000 rpm, and the centrifugation time is 5 min. The vacuum drying temperature is 100℃, and the vacuum drying time is 10 h.

[0076] Example 8

[0077] The difference between this embodiment and Example 1 is as follows: In this embodiment, anhydrous copper chloride solution (0.825 mg) is dispersed in 3 mL of toluene solution. The solvothermal reaction temperature is 85°C, and the reaction time is 1 day; the copper ion solution is added at a dropping rate of 0.2 mL / min; in step 2, the centrifugation speed is 8000 rpm, and the centrifugation time is 15 min. The vacuum drying temperature is 50°C, and the vacuum drying time is 12 h.

[0078] Example 9

[0079] The difference between this embodiment and Example 1 is that the amount of NaBH4 added in this embodiment is 20 mg. The solvothermal reaction temperature is 75℃, and the reaction time is 3 days; the copper ion solution is added at a dropping rate of 1 mL / min; the centrifugation speed in step 2 is 12000 rpm, and the centrifugation time is 10 min. The vacuum drying temperature is 150℃, and the vacuum drying time is 1 h.

[0080] Example 10

[0081] The difference between this embodiment and Embodiment 1 is that: in this embodiment, Ti is prepared... 16 The amount of hexamethylenetetramine used was 0.1g, and the amount of benzoic acid used was 1g.

[0082] Application Example 1

[0083] Take 10 mg of Cu2@Ti prepared in Example 1 16The catalyst was ultrasonically dispersed in a mixed solution of Nafion (commercially available, 100 μL, 5 wt%) and anhydrous ethanol (900 μL) for 30 minutes to form a catalyst ink. 50 μL of the catalyst ink was then uniformly coated onto 1 cm × 1 cm carbon paper (loading 0.5 mg / cm²). -2 After drying, it was used as the working electrode, forming a three-electrode system with an Ag / AgCl reference electrode and a Pt counter electrode. The electrolyte was a mixed solution of 0.1 M KHCO3 and 0.1 M KNO3 in an H-type electrolytic cell (separated by a Nafion 117 membrane). After purging with CO2 for 30 minutes, the reaction was carried out under 395 nm illumination and a constant potential of -0.6 V (vs. RHE).

[0084] After a reaction of 2 hours, the urea yield was determined by the diacetyl monooxime method, and NH3 and NO2 were detected by the salicylic acid method, Griess reagent method, and gas chromatography, respectively. ˉ And byproducts such as CO, CH4, and H2.

[0085] The reaction continued for 10 hours, during which CO2 gas was bubbled in at a rate of 20 mL / min, and samples were taken every 2 hours to detect the urea content and calculate FE.

[0086] Application Example 2

[0087] The difference between this application example and application example 1 is that this application example uses the Cu obtained in example 2. 0.25 @Ti 16 As a catalyst, the reaction was carried out at a constant potential of -0.6V (vs. RHE) for 2 hours.

[0088] Application Example 3

[0089] The difference between this application example and application example 1 is that this application example uses the Cu obtained in example 3. 0.5 @Ti 16 As a catalyst, the reaction was carried out at a constant potential of -0.6V (vs. RHE) for 2 hours.

[0090] Application Example 4

[0091] The difference between this application example and application example 1 is that this application example uses Cu1@Ti prepared in Example 4. 16 As a catalyst, the reaction was carried out at a constant potential of -0.6V (vs. RHE) for 2 hours.

[0092] Application Example 5

[0093] The difference between this application example and Application Example 1 is that this application example uses Cu4@Ti prepared in Example 5. 16 As a catalyst, the reaction was carried out at a constant potential of -0.6V (vs. RHE) for 2 hours.

[0094] Application Example 6

[0095] The difference between this application example and Application Example 1 is that this application example uses Cu8@Ti prepared in Example 6. 16 As a catalyst, the reaction was carried out at a constant potential of -0.6V (vs. RHE) for 2 hours.

[0096] Application Example 7

[0097] The difference between this application example and application example 1 is that the reaction is carried out at a constant potential of -0.3V (vs. RHE) for 2 hours.

[0098] Application Example 8

[0099] The difference between this application example and Application Example 1 is that the reaction is carried out at a constant potential of -0.4V (vs. RHE) for 2 hours.

[0100] Application Example 9

[0101] The difference between this application example and Application Example 1 is that the reaction is carried out at a constant potential of -0.5V (vs. RHE) for 2 hours.

[0102] Application Example 10

[0103] The difference between this application example and Application Example 1 is that the reaction is carried out at a constant potential of -0.7V (vs. RHE) for 2 hours.

[0104] Comparative Example 1

[0105] The method is the same as in Application Example 1, except that Comparative Example 1 uses undoped copper Ti. 16 (10 mg) was used as a catalyst, and the reaction was carried out at a constant potential of -0.6 V (vs. RHE) for 2 hours.

[0106] Comparative Example 2

[0107] The method is the same as in Application Example 1, except that Comparative Example 1 uses CuCl2 (10 mg) as a catalyst and reacts at a constant potential of -0.6 V (vs. RHE) for 2 hours.

[0108] Performance testing

[0109] 1. Take the titanium dioxide clusters Ti obtained in step (1) of Example 1. 16 X-ray single-crystal diffraction analysis of the crystal yielded the following ball-and-stick model structure: Figure 1 As shown in the figure, all Ti are six-coordinated. The sixteen Ti atoms are connected by 24 oxygen atoms to form an octagonal prism structure, with Ti at the vertices and O near the midpoints of the edges, surrounded by 24 benzoic acid atoms.

[0110] The catalyst Cu2@Ti prepared in Example 1 was used 16 Scanning electron microscopy (SEM) was performed, and the resulting spectra are as follows: Figure 2 As shown in the figure, Cu2@Ti 16 It has a relatively clear outline and irregular shape, can be effectively separated, and is expected to be prepared in large quantities, and each Cu2@Ti 16 The Ti, Cu, C, and O elements are evenly distributed in space within the micro-particles.

[0111] 2. The titanium oxide cluster cavity-confined single-atom copper catalysts with different copper contents prepared in Examples 1 to 6 are shown in Figure 3. The powder photograph of Example 1 is shown as 2 eq in Figure 3, the powder photograph of Example 2 is shown as 0.25 eq in Figure 3, the powder photograph of Example 3 is shown as 0.5 eq in Figure 3, the powder photograph of Example 4 is shown as 1 eq in Figure 3, the powder photograph of Example 5 is shown as 4 eq in Figure 3, and the powder photograph of Example 6 is shown as 8 eq in Figure 3. It can be seen from the powder photographs that as the copper content increases, the powder color deepens and the copper content gradually increases.

[0112] To further verify the Cu loading, inductively coupled plasma mass spectrometry (ICP) was used to determine the relative proportions of copper and titanium in the titanium-oxygen cluster cavity-confined single-atom copper catalysts with different copper contents prepared in Examples 1 to 6. The results are as follows: Figure 3b As shown, it can be seen that as the copper content increases, the proportion of copper in the catalyst also increases accordingly.

[0113] 3. Take the titanium dioxide clusters Ti obtained in Example 1 16 Crystal, Cu2@Ti 16 Infrared spectroscopy and Raman spectroscopy were performed, and the results are as follows: Figure 4a , 4b As shown in the figure, Cu2@Ti 16 The FTIR spectrum of the sample and the original Ti 16 The basic match indicates that Ti was introduced during the copper ion process. 16 The molecular skeleton remains unchanged as described above.

[0114] 4. Figure 5 Cu2@Ti obtained in Example 1 16 The extended X-ray absorption fine structure spectra (EXAFS images) of CuO, Cu2O, and Cu foils show that the copper-copper coordination peaks of the copper foil are approximately at [value missing]. At that location, while copper oxide is close to In Cu2@Ti 16 The absence of these peaks in the spectrum indicates that copper does not exist in an aggregated state, but rather in an atomically dispersed state.

[0115] 5. The urea yield after 2 hours of reaction in Application Examples 1, 7 to 10 was determined by the diacetyl monooxime method, and NH3 and NO2 were detected by the salicylic acid method, Griess reagent method and gas chromatography, respectively. ˉ And byproducts such as CO, CH4, and H2, as shown in Figure 6, can be seen that the catalyst (Cu2@Ti) with single-atom copper confined in the cavity of the titanium-oxygen cluster is effective. 16 At -0.6V, the urea yield reached 20.2 mmol / h. -1 g cat -1 The Faraday efficiency is 84.8%. Figure 6c It can be seen that there is a maximum absorption peak at a wavelength of 540 nm, which is the absorption peak of the pink diazine compound formed by the condensation of the product urea and diacetylmonoxime under strong acid and heating conditions. Figure 6d Determination of NO2 by Griess Reagent Method - The maximum absorption peak at 540 nm in the UV-Vis absorption spectrum is due to the interaction between Griess reagent and NO2. - The characteristic peak of the red azo compound produced in the reaction. Figure 6d The UV-Vis absorption spectrum of NH3 determined by the salicylic acid method did not show the characteristic absorption peak of indophenol blue at 650 nm, indicating that the amount of NH3 generated was below the detection limit. Figure 6f The gas chromatogram showed no gaseous product peaks, indicating that there were almost no byproducts such as CO, CH4, and H2.

[0116] 6. To verify the catalyst (Cu2@Ti) confined to a single atom of copper in a titanium-oxygen cluster cavity. 16 The long-term stability of the photoelectrocatalytic synthesis of urea from CO2 and potassium nitrate was demonstrated in Example 1. Urea content was measured every 2 hours during the reaction. The urea content measured at different reaction times was used to calculate the FE (efficiency factor). The results are as follows: Figure 7a , 7b As shown, the current density remains stable even after 10 hours of long-term photoelectrocatalysis, indicating that Cu2@Ti 16 It exhibits excellent stability in photoelectrocatalysis.

[0117] 7. The urea yields of Application Examples 1 to 6, Comparative Examples 1 and 2, after 2 hours of reaction were determined by the diacetyl monooxime method. The results are shown in Figure 8. The figure shows that the urea yield and Faraday efficiency exhibit a typical volcano-like trend with increasing Cu loading. When the Cu / Ti molar ratio reaches 2:16 (i.e., Cu2@Ti...), the yield increases significantly. 16 Urea yield and FE (84.8%) both reached their peak values; while Cu excess (e.g., Cu4@Ti) 16 Performance drops significantly when ( ).

[0118] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A method for preparing a titanium-oxygen cluster cavity-confined single-atom copper catalyst, characterized in that, Includes the following steps: 1) Synthesis of titanium dioxide clusters (Ti 16 Benzoic acid and hexamethylenetetramine were added to a solvent, followed by formic acid. The mixture was stirred, and isopropyl titanate was added to initiate a solvothermal reaction. After the reaction was complete, post-treatment yielded titanium dioxide clusters (Ti). 16 ; 2) Anchoring copper atoms inside the cavity: Under the protection of an inert gas, the titanium oxide clusters Ti obtained in step 1) are anchored... 16 Dispersed in tetrahydrofuran and stirred until dissolved, a reducing agent NaBH4 was added, followed by a degassed copper ion solution. Stirring continued, and after post-treatment, a titanium-oxygen cluster cavity-confined single-atom copper catalyst, i.e., Cu, was obtained. x @Ti 16 catalyst.

2. The preparation method according to claim 1, characterized in that, x can be 0.25, 0.5, 1, 2, 4, or 8.

3. The preparation method according to claim 1, characterized in that, Includes one or more of the following technical features: In step 1), the molar ratio of benzoic acid, hexamethylenetetramine, formic acid, and isopropyl titanate is 12:(0.3-0.5):(1-3):(1.5-3); In step 1), the molar ratio of solvent to isopropyl titanate is (57-115):(1-3); In step 1), the solvothermal reaction temperature is 65℃~85℃, and the reaction time is 1d~5d.

4. The preparation method according to claim 1, characterized in that, The titanium oxide clusters Ti obtained in step 1) 16 The core size is 6nm to 12nm.

5. The preparation method according to claim 1, characterized in that, Includes one or more of the following technical features: Step 2) Titanium oxide clusters Ti 16 The mass ratio of tetrahydrofuran to tetrahydrofuran is 1:(27-67); Step 2) Titanium oxide clusters Ti 16 The mass ratio of NaBH4 to NaBH4 is (4-20):1; The copper ion solution is obtained by dissolving anhydrous copper chloride in a dehydrated organic solvent after vacuum drying. The concentration of the copper ion solution is 0.08–3 mg / mL.

6. The titanium-oxygen cluster cavity-confined single-atom copper catalyst prepared by any one of claims 1 to 5.

7. The application of the titanium-oxygen cluster cavity-confined single-atom copper catalyst prepared by any one of the preparation methods of claims 1 to 5, or the titanium-oxygen cluster cavity-confined single-atom copper catalyst of claim 6, in the photoelectrocatalytic reduction reaction to prepare urea.

8. A method for preparing urea using a photoelectrocatalytic reduction reaction, characterized in that, The titanium-oxygen cluster cavity-confined single-atom copper catalyst prepared by any one of the preparation methods of claims 1 to 5, or the titanium-oxygen cluster cavity-confined single-atom copper catalyst of claim 6, is used as the catalyst.

9. The method as described in claim 8, characterized in that, Includes the following steps: a. The catalyst was dispersed in a mixed solution of Nafion and anhydrous ethanol to prepare a catalyst ink. The catalyst ink was uniformly coated on carbon paper and dried to serve as the working electrode. Ag / AgCl was used as the reference electrode and Pt was used as the counter electrode to form a three-electrode system. b. In an H-type electrolytic cell, an electrolyte is added, and under a high-purity CO2 atmosphere, urea is synthesized by co-reduction coupling of carbon dioxide and nitrate ions through light irradiation and periodic pulse voltage treatment.

10. The method as described in claim 9, characterized in that, Includes one or more of the following technical features: The mass ratio of catalyst to Nafion is (1–20):(27.5–110); The illumination conditions are: λ≤400nm, light intensity 142mW / cm². 2 Irradiation under ultraviolet light, with a photoreaction time of 2h-20h and a phototemperature of 25±2℃; The periodic pulse voltage is -0.7V to -0.3V vs. RHE.

Citation Information

Cited By

  • Method for electrocatalytic synthesis of urea based on multi-size Cu-based metal catalyst

    CN122039075A